Characteristics of Somatometric Indicators at Urban Schoolchildren - Kurbanov Abdulaziz Shaniyazovich; Dustov Karim Turayevich; Khodiyeva Farangizoy Rahmat kizi (Genius Publishing Group, 2022)
The article presents the results of a study of urban schoolchildren. A number of somatometric parameters of schoolchildren of different ages were studied and compared with the norm. Based on the results obtained, conclusions were made and appropriate recommendations were made.
Keywords: Physical development; body weight; body height; somatometric